DEVELOPMENT OF CREATIVE ECONOMY BASED ON SHARIA PRINCIPLES IN ENCOURAGING ECONOMIC INDEPENDENCE OF THE PEOPLE - Sitti Aisyah; Nur Diana Cholidah (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2025)
This research aims to analyze the development of the creative economy based on sharia principles in encouraging the economic independence of the people. The approach used is qualitative with the library research method, which is sourced from scientific journals, books, and institutional reports related to creative economy and sharia economics. The data analysis technique uses content analysis with a descriptive-analytical approach. The results of the study show that the creative economy has great potential in improving people's welfare through job creation and income increase, especially in the micro, small, and medium enterprises (MSMEs) sector. The integration of sharia principles, such as justice, honesty, trust, and halal products, provides added value in building consumer trust and maintaining business sustainability. In addition, the sharia-based creative economy contributes to strengthening the economic independence of the people through community-based empowerment and the optimization of local potential. However, the development of a sharia-based creative economy still faces various challenges, including low sharia economic literacy, limited access to financing, and the lack of optimal use of digital technology. Therefore, synergy is needed between the government, Islamic financial institutions, and business actors in creating a supportive ecosystem. With the right strategy strengthening, the sharia-based creative economy has the potential to become the main instrument in realizing sustainable and equitable economic independence for the people.